(untitled) (Iranian Journal of Kidney Diseases, 2014)
Introduction. Recent studies report reduced vascular compliance and elevated levels of fibroblast growth factor 23 (FGF23) in patients with autosomal dominant polycystic kidney disease (ADPKD) and preserved kidney function. In the present study, we investigated the relationship between vascular compliance and FGF23 in patients in early phases of ADPKD. Materials and Methods. We studied 54 ADPKD patients with preserved kidney function and 24 healthy individuals. All participants underwent noninvasive pulse wave analysis in order to determine large arterial elasticity index (LAEI) and small arterial elasticity index (SAEI) using a modi?ed Windkessel model. Levels of FGF23 in addition to several cardiovascular risk factors were evaluated. Linear regression analyses were performed to determine independent correlates of LAEI, SAEI, and FGF23. Results. In the ADPKD group, 33 patients were hypertensive and the remaining patients were normotensive. Serum FGF23 levels of both ADPKD groups were significantly higher than that in the controls. Both hypertensive and normotensive ADPKD patients had lower LAEI and SAEI levels compared to the controls. There was no significant correlation between vascular compliance parameters and FGF23 levels. Having ADPKD was independently associated with increased FGF23 levels and decreased SAEI. Conclusions. Fibroblast growth factor 23 was found substantially elevated and arterial compliance was found significantly decreased in early ADPKD patients regardless of hypertension. However, there was no significant correlation between FGF23 levels and arterial function parameters. Additional studies are required to determine possible mechanisms of these disturbances and cardiovascular effects of FGF23 in ADPKD patients.